TITLE: KNOWLEDGE AND CURRENT PRACTICE OF HEALTH PROFESSIONALS IN NOISE INDUCED HEARING LOSS MANAGEMENT - Ling, Leu Yee; Wahat, Nor Haniza Abdul; Ishak, Wan Syafira (International Journal of Allied Health Sciences, 2019)
Introduction: The purpose of this study is to identify knowledge and current practice among health professionals involved in the management of noise induced hearing loss (NIHL). Methods: Thirty eight health professionals (i.e occupational health (OH) doctors, ear, nose and throat (ENT) specialists and audiologists participated in the study. Results: We found no significant difference among the health professionals’ knowledge in NIHL, [F(2, 35)=1.44, p>0.05]. With reference to current practices, it was found that 90% of OH doctors and 100% of ENT specialists used pure tone audiometry’s (PTA) results in diagnosing NIHL. In comparison, 30% of audiologists conducted both PTA and otoacoustic emission (OAE) test, as OAE is more sensitive to subtle cochlear changes. ENT specialists have higher perception and acceptance level towards audiologist’s role compared to OH doctors, U=11.00, p<0.05. This indicate that most OH doctors did not regard audiologists as key professionals to lead hearing conservation program.